Decreased calcineurin immunoreactivity in the postmortem brain of a patient with schizophrenia who had been prescribed the calcineurin inhibitor, tacrolimus, for leukemia - Wada A; Kunii Y; Matsumoto J; Hino M; Nagaoka A; Niwa S; Yabe H (Neuropsychiatric Disease and Treatment)
Akira Wada,1,2 Yasuto Kunii,1 Jyunya Matsumoto,1 Mizuki Hino,1 Atsuko Nagaoka,1 Shin-ichi Niwa,3 Hirooki Yabe1 1Department of Neuropsychiatry, Fukushima Medical University School of Medicine, Fukushima City, Fukushima, 2Department of Neuropsychiatry, The University of Tokyo Hospital, Bunkyo-ku, Tokyo, 3Department of Psychiatry, Aizu Medical Center, Fukushima Medical University, Aizuwakamatsu City, Fukushima, Japan Background: The calcineurin (CaN) inhibitor, tacrolimus, is widely used in patients undergoing allogeneic organ transplantation and in those with certain allergic diseases. Recently, several reports have suggested that CaN is also associated with schizophrenia. However, little data are currently available on the direct effect of tacrolimus on the human brain.Case: A 23-year-old Japanese female experienced severe delusion of persecution, delusional mood, suspiciousness, aggression, and excitement. She visited our hospital and was diagnosed with schizophrenia. When she was 27 years old, she had severe general fatigue, persistent fever, systemic joint pain, gingival bleeding, and breathlessness and was diagnosed with acute myelomonocytic leukemia. Later she underwent bone marrow transplantation (BMT), she was administered methotrexate and cyclosporin A to prevent graft versus host disease (GVHD). Three weeks after BMT, she showed initial symptoms of GVHD and was prescribed tacrolimus instead of cyclosporin A. Seven months after BMT at the age of 31 years, she died of progression of GVHD. Pathological anatomy was examined after her death, including immunohistochemical analysis of her brain using anti-CaN antibodies. For comparison, we used our previous data from both a schizophrenia group and a healthy control group. No significant differences were observed in the percentage of CaN-immunoreactive neurons among the schizophrenia group, healthy control group, and the tacrolimus case (all P>0.5, analysis of covariance). Compared with the healthy control group and schizophrenia group, the percentages of CaN-immunoreactive neurons in layers III–VI of the BA46 and the putamen tended to be lower in the tacrolimus case.Conclusion: Tacrolimus may decrease CaN immunoreactivity in some regions of the human brain. Thus, tacrolimus may introduce side effects such as cognitive dysfunction and extrapyramidal symptoms. In addition, we also found that the effect of tacrolimus on CaN immunoreactivity in human brain was stronger than the effect of schizophrenia. Keywords: calcineurin, calcineurin inhibitors, schizophrenia, postmortem brain, immunohistochemistry